Voices from student teachers in New York: The persistence of a subtractive experience of the edTPA as a licensure exam for initial certification - Clayton, Christine D. (Education Policy Analysis Archives, 2018)
This article explores how candidates’ experiences in multiple initial certification programs within a single School of Education evolved over the first three semesters of New York’s implementation of edTPA as a requirement for initial licensure. The data reviewed included primarily surveys and interviews of teaching candidates, framed by critical perspectives on accountability, teacher performativity, and constructivist theories on learning to teach. Results suggest candidates’ perceptions of program alignment and edTPA benefits improved while several challenges persisted. These included the lack of mentor teacher knowledge about the edTPA as well as disconnects between candidates’ edTPA scores and local program evaluations. Additionally, student teachers’ perceptions of a subtractive experience of the edTPA continued in spite of improved perceptions about the benefits of the exam and across all scoring levels, programs, and semesters. A discussion of these results considers the implication of policies that reify quality, compel performance management, and contribute to values conflict for candidates in the particularly unique developmental moment of learning to teach. These voices of student teachers, often underrepresented in the research on edTPA, urge a reconsideration of the policy on teacher performance assessments in terms of how such policies impact the experiences of those learning to teach.